COMPARISON OF PHYTOCHEMICAL SCREENING AND BIOLOGICAL ACTIVITIES OF AQUEOUS AND ALCOHOLIC FRACTIONS OF PTEROSPERMUM ACERIFOLIUM (LEAF PETIOLE) - Ahmed, Wasim; SANIA FEROZ; SADAF AFREEN; ARFAN ULLAH (Innovare Journal of Sciences, 2016)
ABSTRACT Objectives:The objective of the current work was to compare the two fractions (aqueous and alcoholic) of leaf petioles of Pterospermum acerifolium. The two fractions were compared for their phytochemistry and biological activities (antioxidant, antibacterial and antifungal). Methods:phytochemistry was done using conventional natural products identification tests. Antioxidant activity was done using DPPH free radical scavenging assay. Similarly, anti-fungal and anti-bacterial assays were performed using agar tube dilution and agar well diffusion assays respectively. Results:Phytochemical screening, using conventional natural products identification tests indicated the presence of different phytoconstituents. The phytoconstituents present in methanolic extract were tannins, saponins, steroids, terpenoids, coumarins and betacyanins while aqueous extract contains tannins, glycosides, reducing sugar, saponins, steroids, terpenoids, coumarins and betacyanins. Both the extracts were analyzed for antioxidant activity. The aqueous extract showed significant activity as compared to methanolic extract.The same two fractions were compared for their antibacterial and antifungal activities. Conclusion:The methanolic and aqueous extracts obtained from P. acerifolium shows strong activity against most of the tested fungal and bacterial strains It is concluded that methanolic extract showed significant activity against fungal strains as compared to aqueous extract whereas antibacterial activity of aqueous extract is more active than methanolic extract. Efforts should be made to isolate and derive active compounds responsible for these activities. Phytochemistry, Antioxidant activity,Antibacterial activity,Antifungal activity